Cerebral cortical thickness in chronic pain due to knee osteoarthritis: the effect of pain duration and pain densitization - Alshuft, Hamza; Condon, Laura; Dineen, Robert A.; Auer, Dorothee P. (Public Library of Science, 2016)
Objective